The Comancheros [videorecording (DVD)] - Curtiz, Michael, 1886-1962; Wayne, John, 1907-1979; Whitman, Stuart; Wellman, Paul I. (Paul Iselin), 1898-1966 (Twentieth Century Fox Home Entertainment, 2003)
Texas Ranger Jake Cutter (Wayne) arrests gambler Paul Regret (Whitman) but soon finds himself teamed with his prisoner in an undercover effort to defeat a violent band of gunrunners and thieves known as the Comancheros. The last film of director Michael Curtiz (Casablanca).